Implementasi Penilaian dan Pengawasan Lembaga Pendidikan Anak Usia Dini - Azian, Nurul (STAI Auliaurrasyidin Tembilahan, 2022)
The ECCE management often finds obstacles, including a lack of understanding of management, non-professional teaching staff, inadequate infrastructure, and so on. This study aims to identify the implementation of the management at the ECCE Azzahra, East Lampung. This research is qualitative research by adopting the Milles and Huberman model, namely: data collection, data reduction, data presentation, and drawing conclusions. Data was collected by using structured interviews and documentation. The results revealed that the implementation of the management at the ECCE Azzahra, East Lampung had been carried out in accordance with the theory. This was proved by the assessment – based on the instruments that have been made – carried out by the principal once a week. The assessment and supervision include the performance of teachers and staff at PAUD Azzahra, East Lampung. The findings were then evaluated and presented in weekly meetings to teachers and staff.